Comparison of Surface Roughness and Microhardness of Reinforced Glass Ionomer Cements and Microhybrid Composite - Turgut, Hacer; Karakaş, Seda Nur; Küden, Cihan (UI Scholars Hub, 2021)
Objectives: The purpose of this study was to compare high viscosity glass ionomer cement (HVGIC), giomer and microhybrid composite using the atomic force microscopy (AFM) and Vickers microhardness. Methods: Three different restorative materials Equia Forte (HVGIC), Beautifil II (giomer) and Solare X (microhybrid composite) were used in this study. A total of 30 samples were prepared, 10 of each of the restorative materials used in our study. Samples were prepared using standard cylindrical Teflon molds with a diameter of 8 mm and a height of 2 mm. The measurements of surface roughness and hardness were performed by using AFM and Vickers microhardness, respectively. The surface roughness was analyzed using the Kruskal Wallis test. One-way variance analysis (ANOVA) and LSD test was used for the surface hardness (α = 0.05). Results: There was no significant difference between the groups according to surface roughness values (p> 0.05). A statistically significant difference was found between all groups in terms of surface hardness. Conclusion: Reinforced glass ionomer cements had similar and surface properties than composite resin.